Medically Unexplained Symptoms and Attachment Theory: The BodyMind Approach® - Payne, Helen; Brooks, Susan D. (Frontiers in Psychology, 2019)
This article discusses how The BodyMind Approach® (TBMA) addresses insecure attachment styles in medically unexplained symptoms (MUS). Insecure attachment styles are associated with adverse childhood experiences (ACEs) and MUS (Adshead & Guthrie, 2015) and affect sufferers’ capacity to self-manage. The article goes on to make a new hypothesis to account for TBMA’s effectiveness (Payne & Brooks, 2017), that is, it addresses insecure attachment styles, which may be present in some MUS sufferers, leading to their capacity to self-manage. Three insecure attachment styles (dismissive, pre-occupied and fearful) associated with MUS are discussed. TBMA is described and explanations provided of how TBMA has been specifically designed to support people’s insecure attachment styles. Three key concepts to support insecure attachment styles involved in the content of TBMA are identified and debated: a) emotional regulation; b) safety; and c) bodymindfulness. There is a rationale for the design of TBMA as opposed to psychological interventions for this population. The programme’s structure, facilitation and content, takes account of the three insecure attachment styles above. Examples of how TBMA works with their specific characteristics are presented. TBMA has been tested and found to be effective during delivery in the United Kingdom National Health Service (NHS). Improved self-management has potential to reduce costs for the NHS and in General Practitioner time and resources.